ANALISIS MEKANISME PEMBUBARAN ORMAS BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2017 TETANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 2 TAHUN 2017 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 17 TAHUN 2013 TENTANG ORGANISASI KEMASYARAKATAN MENJADI UNDANG-UNDANG DITINJAU DALAM PERSPEKTIF NEGARA HUKUM DAN DEMOKRASI DI INDONESIA - Nadia Dwi Anjulina; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The dissolution of social organizations which are the absolute authorityof the Government based on Law Number 16 of 2017 concerning Stipulation ofGovernment Regulations in Lieu of Law Number 2 of 2017 concerningAmendments to Law Number 17 of 2013 concerning Social Organizations intoLaws does not reflect the basic principles of a rule of law and democracy thatrequires the protection of human rights and the distribution of power in orderto prevent the instrumentation process from placing the law as part of power.The dissolution of social organizations should still involve a court process toavoid subjective decisions made by the government. Therefore, the purpose ofthis thesis research is first, to analyze the mechanism for dissolution of socialorganizations based on Law Number 16 of 2017 concerning Stipulation ofGovernment Regulations in Lieu of Law Number 2 of 2017 concerningAmendments to Law Number 17 of 2013 concerning Social Organizations intoLaws which is reviewed from the perspective of the rule of law and democracyin Indonesia. Second, the ideal arrangement for the dissolution of cocialorganizations in IndonesiaThis type of research can be classified into normative juridicalresearch, namely a research that describes clearly and in detail the mechanismfor the dissolution of social organizations based on Law Number 16 of 2017concerning Stipulation of Government Regulations in Lieu of Law Number 2 of2017 concerning Amendments to Law Number 17 of 2013 concerning SocialOrganizations into Laws, which is reviewed from the perspective of a rule oflaw and democracy in Indonesia. This study uses data sources in the form ofprimary data and secondary data, and data collection techniques are carriedout by literature review.From the results of the research problem there are two main things thatcan be concluded. First, the problem of fulfilling human rights in themechanism for dissolving social organizations in Indonesia. Second, the idealarrangement is related to the mechanism for the dissolution of SocialOrganizations in Indonesia. The author's suggestion is that the current Law onSocial Organizations needs to be revised again by incorporating the court'sauthority in deciding disputes over the dissolution of social organizationswhich is supported by the application of fast, simple and low-cost judicialprinciples.Say key: Social Organization-Rule of Law-Democracy